The Narrativization of an Unusual Event at the Belgrade Zoo: A Semiotic Analysis of The Story of Gabi the Dog and the Jaguar - Sonja Žakula (University of Belgrade, 2016)
The paper offers a semiotic analysis of the narrative of Gabi the dog and the jaguar in the form in which the story appears on the website of the Belgrade zoo. I believe that it is valid to assume that an analysis of this narrative can provide a window into the ways in which meanings of concepts such as ‘wildness’, ‘domesticity’, ‘freedom’, ‘captivity’ and ultimately, ‘nature’ and ‘culture’ are articulated within the context of this institution. On the one hand, I will base the paper on ideas articulated in the field of human-animal relations, and on the other on the methodological postulates of semiotic analysis introduced by Algirdas Julien Greimas and further developed by Dragana Antonijević. The aim of the paper is to, by applying semiotic analysis to the way in which an unusual event at the zoo was narrativized, uncover the deeper structure of thought which underlies the story and reflects and shapes not just the discourse of the Belgrade zoo, but the implicit understanding of the role and function of zoos in Serbia up until the present day.